LANGUAGE, SPORT, SUSTAINABLE DEVELOPMENTCLASH OR FIT - Danica, Pirsl (European Scientific Journal, ESJ, 2014)
Aspect of Sport as a Tool for Sustainable Development and Solidarity implies that toolkits should be created for NOCs in developing countries to assist them in developing opportunities to promote sustainable development, and in developing appropriate action plans to address their particular priorities and challenges. The IOC Sport and Environment Commission, through the Olympic Solidarity programs should assist NOCs in the formulation and implementation of sport and environmental projects. The IOC and partners should develop and produce guidelines for feasible projects at the national level. Sport should be used in addressing other social and economic priorities such as the fight against poverty and the spread of HIV/AIDS, and in the promotion of social justice, human well-being and gender equality. Indispensable factor in this game should be observed as well, and that is “clean language “ or the language used to define all the aspects of sport, language and sustainable development.